Studies on Sorption Tendency and Permeability of Different Cold Drinks Across Urinary Bladder Membranes - Shukla, P.C.; Singh†, S.N.; Shukla, Aalok; Gupta, C.P. (Asian Journal of Chemistry, 2010)
Density, viscosity, pH, absorbance, water contents and hydrodynamic permeability of Aqua guard water, Aqua fina water, Mountain dew, Mirinda, Pepsi and Thums up have been measured across urinary bladder membranes of goat. It has been found that different coloured permeants are absorbed in the membrane texture and produce decisive effects in the permeability of the urinary bladder membranes. By keeping the permeants for a few hours in the urinary bladder, Mirinda and Mountain dew colourize the bladder surface with their colours while blackish colour is observed for Pepsi and black brownish tinge is observed in Thums up. Practically no change in colour is observed when bladder is immersed in urine solution. Absorption in the bladder surface will have adverse effects in structural properties of the bladder. Since urinary process may be defined as a process of development of pressure, sustenance of pressure and finally release of pressure, such studies are expected to be a great use in predicting physiological behaviour of the membrane in diverse situations.